(untitled) (Revista de Investigaciones Universidad del Quindío, 2014)
In this article we propose a digital modulation scheme called Partitioned Modulation of 4 States in 3 Dimensions (4P-3D). Such scheme splits the binary message in 2-bit blocks and represents each block through a real vector of 3 components. The points of constellation match with vertices of a regular tetrahedron centered on origin. The modulation basis set is formed by 3 functions taken from an orthonormal wavelet family. Theoretic analyses and simulations results show that 4P-3D modulation has better performance against noise than binary pulse amplitude modulation (2-PAM) over additive white Gaussian noise channels (AWGN). Moreover, the modulated signal shaping from wavelets allows that synchronism errors over detection of samples be negligible on the bit error probability. An adverse aspect of 4P-3D is a reduction of spectral efficiency with respect to that 2-PAM.